Competitiveness by Requisitely Holistic and Innovative Logistic Management - Knez, Matjaž; Rosi, Bojan; Mulej, Matjaž; Lipičnik, Martin (Promet - Traffic&Transportation, 2010)
In the age of global expansion of business operations and contemporary way of life the material and information flows in and between different companies are growing rapidly; they are thus becoming more and more difficult to manage. Had business functions in companies been dealt with separately until now (purchase, production, finances, sale, etc.), today the emphasis is placed on their integration due to their interdependence. By studying supply chains inside and between business partners, companies can gain competitive advantage and become more adjustable, taking the increasingly changing market circumstances into account. This enables them to meet consumers’ demands and expectations requisitely holistically. Taking all the crucial activities into account, the logistics management plays a key role in the companies facing the challenges of the new millennium. Based on the numerous megatrends, which influence each and every business entity, this article aims to explain the increasing strategic importance of logistics management. The latter may not be dealt with one-sidedly as a cost; moreover, the key aspects such as competitiveness as well as long–term existence of a company must also be considered. Innovation and systemic thinking in it and about it are needed. KEY WORDS: logistics management, logistics strategy, supply chains, megatrends, innovation, systemic thinking